The Effect of Social Support and Moral Identity on Meaning in Life of Hijrah Youth: Pengaruh Dukungan Sosial dan Identitas Moral terhadap Makna Kehidupan Pemuda-Pemudi Hijrah - Marliani, Rosleny; Buzairimi Anwar, Asep; Sudirman, Deden; Irawan, Feri Indra (Universitas Islam Indonesia, 2023)
The need for life’s meaning remains important for most individuals, particularly for Hijrah youth who aspire to embark on a transformative journey. However, these individuals often face a lack of support from their environment during the Hijrah process. In this context, moral identity assumes a significant role as an individual factor, serving as a guiding reference. Therefore, it is necessary to examine how social support and moral identity shape the meaning of life for Hijrah youth. This research aims to investigate the impact of social support and moral identity on the meaning of life among Hijrah youth. The method used in this study is quantitative, and the sampling technique employed is purposive sampling with a sample size of 255 individuals who are young people currently in the process of Hijrah, involved in communities, and Hijrah study groups. The results of this study showed that both social support and moral identity had a significant influence on the meaning of life. The combined contribution of these factors was measured at 16%. Furthermore, young individuals who embarked on the Hijrah journey and had good social support and a well-formed moral identity benefited in the formation of a better meaning of life during their Hijrah, unlike individuals with unstable moral identities. Additionally, it was expected that the environment provided support throughout the Hijrah process as a positive influence.